2015
DOI: 10.1080/23294515.2015.1021494
|View full text |Cite
|
Sign up to set email alerts
|

Lay attitudes toward deception in medicine: Theoretical considerations and empirical evidence

Abstract: Background: There is a lack of empirical data on lay attitudes toward different sorts of deception in medicine. However, lay attitudes toward deception should be taken into account when we consider whether deception is ever permissible in a medical context. The objective of this study was to examine lay attitudes of U.S. citizens toward different sorts of deception across different medical contexts. Methods: A one-time online survey was administered to U.S. users of the Amazon "Mechanical Turk" website. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Description as inactive drug, and giving no description or description as pharmacologically active drug with delayed disclosure were less acceptable (apparently because of reduced benefit), whereas description as pharmacologically active drug and giving no description were the least acceptable actions. The data are consistent with previous results32 and indicate that, for our respondents, the act itself is also important (although less important than its consequences), deception that creates false belief is worse than deception that negates or blocks true belief, and outright lying is different and worse than non-lying deception.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Description as inactive drug, and giving no description or description as pharmacologically active drug with delayed disclosure were less acceptable (apparently because of reduced benefit), whereas description as pharmacologically active drug and giving no description were the least acceptable actions. The data are consistent with previous results32 and indicate that, for our respondents, the act itself is also important (although less important than its consequences), deception that creates false belief is worse than deception that negates or blocks true belief, and outright lying is different and worse than non-lying deception.…”
Section: Discussionsupporting
confidence: 91%
“…“Acceptable if benefit to patient large”, “Acceptable if no harm to patient”, “Acceptable with moderate benefit to patient”, and “Acceptable with large benefit to other patients” were among the five most agreeable statements. This is consistent with the results of previous studies that, using different methodology and studying Western populations, showed acceptability of placebo treatment to patients and the general public,21,32,34,35 the philosophical approach used by some defenders of placebo treatment,24 the notion of good being more basic than the notion of right, and the precedence of “care/harm” as a psychological foundation of morality over other foundations 46…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In one study, 50–84% of the participants indicated that if they were informed about the potential benefit of placebo effects in treatment, they deemed placebo treatment acceptable [ 15 ]. However, data from other studies reported more nuances in attitudes, where participants reported this to be strongly dependent on factors such as the type of a condition [ 11 , 17 ]. Another recurrent topic from these patient studies was the need for transparency and shared decision-making [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%